Productivity with Health, Safety, and Environment Select Proceedings of HWWE 2019 - Singh, Lakhwinder Pal.; Bhardwaj, Arvind; Iqbal, Rauf.; Khanzode, Vivek; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This volume comprises select proceedings of the International Conference on Humanizing Work and Work Environment organized by the Indian Society of Ergonomics (HWWE2019). The book presents research findings on different areas of ergonomics for developing appropriate tools and work environment considering capabilities and limitations of working people for maximum effectiveness on their performance. This volume will be of interest to academics, professionals and practitioners in the field of ergonomics. .
Exposure to peak sound pressure levels in military fieldfire ranges -- Ergonomically designed job table for reducitn MSD Symptoms of welders -- Soft Ssuability problem in cosumer electronic products -- A systematic literature review on virtual reality based fire-safety training in India -- Prevalence of occupational risk factors in commercial weaving -- A study on the impact of prolonged sitting on a computer workstation User well-being and productivity -- To study the stress management of women police in Pune Urban Area -- Effects of ddifferent types of noise on Human Cognitive Performance.
Keywords: Industrial engineering; Production engineering; Engineering design; Personnel management; Occupational health services; User interfaces (Computer systems).; Human-computer interaction; Human physiology; Industrial and Production Engineering; Engineering Design; Human Resource Management; Occupational Health; User Interfaces and Human Computer Interaction; Human Physiology; Human engineering -- Congresses; Industrial productivity -- Congresses; Industrial hygiene -- Congresses; Industrial safety -- Congresses